Nonperturbative QCD thermodynamics in the external magnetic field - M. A. Andreichikov; Yu. A. Simonov (European Physical Journal C: Particles and Fields, 2018)
Abstract The thermodynamics of quarks and gluons strongly depends on the vacuum colormagnetic field, which grows with the temperature T, so that spatial string tension $$σ _s =const~ g^4 (T) T^2$$ σs=constg4(T)T2 . We investigate below what happens when one imposes in addition constant magnetic field and discover remarkable structure of the resulting thermodynamic potential.